The Standard of Care Definitions on COVID-19 Pharmacological Clinical Trials: A Systematic Review - Addis, Antonio; Amato, Laura; Cruciani, Fabio; Saulle, Rosella; De Crescenzo, Franco; Mitrova, Zuzana; Vecchi, Simona; Perrone, Francesco; Davoli, Marina (Frontiers in Pharmacology, 2021)
Background: Standard of Care (SoC) has been used with different significance across Randomized Clinical Trials (RCTs) on the treatment of Covid-19. In the context of a living systematic review on pharmacological interventions for COVID-19, we assessed the characteristics of the SoC adopted in the published RCTs. Methods: We performed a systematic review searching Medline, Pubmed, Embase, Cochrane Covid-19 register, international trial registers, medRxiv, bioRxiv, and arXiv up to April 10, 2021. We included all RCTs comparing any pharmacological intervention for Covid-19 against any drugs, placebo, or SoC. All trials selected have been classified as studies with SoC including treatments under investigation for COVID-19 (SoC+); studies with SoC without specifications regarding the potential therapies allowed (SoC-); studies including as control groups Placebo (P) or active controls (A+). Results: We included in our analysis 144 RCTs, comprising 78,319 patients. Most of these trials included SoC (108; 75.0%); some in all arms of the study (69.7%) or just as independent comparators (30.3%). Treatments under investigation for COVID-19 in other trials were included in the SoC (SoC+) in 67 cases (62.0%), Thirty-one different therapeutic agents (alone or in combination) were counted within the studies with SoC+: mostly hydroxychloroquine or chloroquine (28), lopinavir/ritonavir (20) or azithromycin (16). No specification was given regarding treatment allowed in the control groups (SoC-) in 41 studies (38.0%). Conclusion: Our analysis shows that the findings emerging from several clinical trials regarding the efficacy and safety of pharmacological intervention for COVID-19 might be jeopardized by the quality of control arms.